Taxonomy and Methods of Estimation of Investment in Human Capital: Practical Practices - Poudel, Min Raj (Journal of TESON, 2026)
The investment in human capital is the sum of all types of education costs. It reflects the economic burden on pupils or their parents, the government, and donor agencies for gaining and providing education and skills to the people. The main objective of this study is to analyze the taxonomies and methods of estimation in investment and how fixed asset depreciation is applied in calculating capital investment in educational institutions. The analysis concludes there are several taxonomies of investment, and some overlap with each other in meaning. In practice, these concepts are broadly categorized into private, institutional, and social. The ingredient approach is practically used to analyze these taxonomies. The diminishing balance is considered the best method for estimating the depreciation value of the capital assets. The useful life of assets and the rate of depreciation should be standardized and defined using real sources. Without separate analyses of private and social investments in human capital, allocative efficiency analysis is impossible.